Linguistic studies and developments of the names of works of art (Eurasian Journal of Learning and Academic Teaching, 2023)
Article describes the finding a suitable variant of lexemes in the process of translation, distinguishing real and lacunar units between languages is an important task of research in the direction of linguo-cultural studies. Symbolic words figuratively serve to increase the attractiveness and effectiveness of speech, illuminate the essence of events, and provide an artistic image.